Haplotype Variations and Evolutionary Analysis of the Granule-Bound Starch Synthase I Gene in the Korean World Rice Collection - Maung, Thant Zin; Yoo, Ji-Min; Chu, Sang-Ho; Kim, Kyu-Won; Chung, Ill-Min; Park, Yong-Jin (Frontiers in Plant Science, 2021)
Granule-bound starch synthase I (GBSSI), responsible to encode the Waxy gene, is involved in the amylose synthesis step of starch biosynthesis. We investigated the genotypic and haplotypic variations of GBSSI ((Os06g0133000) gene including its evolutionary relatedness in nucleotide sequence level using SNPs, indels and SVs called from 475 Korean World Rice Collection (KRICE_CORE) which was made up of 54 wild rice and 421 cultivated represented by 6 ecotypes (temperate japonica, indica, tropical japonica, aus, aromatic and admixture) or in another way by 3 varietal types (landrace, weedy and bred). The results revealed that 27 of 59 haplotypes indicated a total of 12 functional SNPs (fSNPs), identifying 9 novel fSNPs. According to the identified novel fSNPs, we classified the entire rice collection into 3 groups: cultivated, wild and mixed (cultivated and wild) rice. Five novel fSNPs were localized in wild rice: four G/A fSNPs in exons 2, 9 and 12 and one T/C fSNP in exon 13. We also detected three previously reported fSNPs, namely, a G/A fSNP (exon 4), an A/C fSNP (exon 6) and a C/T fSNP (exon 10), which were observed only in cultivated rice, while an A/G fSNP (exon 4) was observed exclusively in wild rice. All-against-all comparison of four varietal types or six ecotypes of cultivated rice with wild rice showed that the GBSSI diversity was higher only in wild rice ( = 0.0056). Diversity reduction in cultivated rice can be useful to encompass the origin of this gene GBSSI during its evolution. Significant deviations of Tajima’s D values from neutral model, namely positive values of wild and indica under balancing selection together with their reverse negative values by both japonicas undergone from purifying selection can be informative about the selective events of GBSSI genomic insights. Despite the estimation differences in population structure and PCA between wild and sub-divided cultivated subgroups, the inbreeding effect was quantified by FST statistic, signifying genetic relatedness of GBSSI. Our findings of wild novel fSNPS can be applicable for future breeding of waxy rice varieties. Furthermore, signatures of selective sweep can also be of informative into further deeper insights during domestication.